Persisting narratives undermine potential water scarcity solutions for informal areas of Mexico City: the case of two settlements in Xochimilco. Issue 6 (18th August 2021) - Hernández Aguilar, Bertha; Lerner, Amy M.; Manuel-Navarrete, David; Siqueiros-García, J. Mario
ABSTRACT: In Global South megacities, hazards related to climate change – such as water scarcity – are exacerbated by informal urban development. Limited access to public services, particularly those such as water which are considered human rights, require alternative solutions, each with its own trade-offs and costs. Cities' decisions are often guided by socially constructed narratives.  This research explores three existing narratives on promoting water scarcity solutions in two informal communities of the Xochimilco municipality in Mexico City: (1) 'formalizing informality' (e.g., promoting grey infrastructure development); (2) 'enhancing informality' (e.g., improving the current system of delivery by water trucks); and (3) greening informality (e.g., capturing rainwater).